Peran Patroli Roda Dua Unit Patroli Satuan Sabhara Polres Garut Dalam Mencegah Tidak Pidana Curanmor Roda Dua Di Kabupaten Garut - Primadyantara Muaz (Police Studies Review, 2020)
This research is motivated by the criminal act of motor vehicle theft in the Garut police area which is still high, especially two-wheeled curanmor with the last 3 years increasing numbers. Repressive measures only resolve criminal acts that have occurred where the victim already exists and the loss suffered by the victim. Therefore, preventive efforts are better carried out by the Sabhara unit, so that the important point is the role of the Sabhara Unit, therefore research is conducted to find out the Role of Sabhara members in the implementation of Patrol, the factors that influence the implementation of this patrol towards the prevention of acts criminal motor vehicle theft. This research method uses a qualitative approach. Using descriptive analysis research methods, and was chosen because the results of the study in the form of translation and explanation. Data collection techniques by interview, observation, and document review. Meanwhile, teknk the validity of the results of research using data triangulation techniques. Based on the results of research that the efforts carried out by the Sabhara Police Garut Unit Patrol Unit are still not optimal or still have constraints in their implementation due to lack of several things such as infrastructure facilities, the number of patrol members, the budget, the number of police officers who implement dikjur, and public concern for environmental security . So that researchers have a suggestion that it is necessary to foster the ability of all patrol officers through appropriate planning and organization in the implementation of patrols and controllers are actively involved to control and supervise the implementation of patrols.